Preservation of microvascular integrity and immunomodulatory property of prevascularized human mesenchymal stem cell sheets. (28th January 2021) - Jia, Wenkai; Sharma, Dhavan; He, Weilue; Xing, Qi; Zhao, Feng
Abstract: Prevascularization is essential to ensure the viability, functionality, and successful integration of tissue‐engineered three‐dimensional (3D) constructs with surrounding host tissues after transplantation. Human mesenchymal stem cell (hMSC) sheet can be prevascularized by coculturing with endothelial cells (ECs), and then be further used as building blocks for engineering 3D complex tissues. In addition, predifferentiation of hMSCs into a tissue‐specific lineage in vitro has been proven to promote graft engraftment and regeneration. However, it is unclear if the prevascularized hMSC sheets can still maintain their microvascular integrity as well as the immune‐regulatory properties after their tissue‐specific differentiation. The objective of this study was to investigate the effects of differentiation cues on the microvascular structure, angiogenic factor secretion, and immunogenic responses of prevascularized hMSC sheets. The results showed that upon coculturing with ECs, hMSC sheets successfully formed microvascular network, while maintaining hMSCs' multi‐lineage differentiation capability. The next step, osteogenic and adipogenic induction, damaged the preformed microvascular structures and compromised the angiogenic factor secretion ability of hMSCs. Nonetheless, this effect was mitigated by adjusting the concentration of differentiation factors. The subcutaneous transplantation in an immunocompetent rat model demonstrated that the osteogenic differentiated prevascularized hMSC sheet preserved its microvascular structure and immunomodulatory properties comparable to the undifferentiated prevascularized hMSC sheets. This study suggested that a balanced and optimal differentiation condition can effectively promote the tissue‐specific predifferentiation of prevascularized hMSC sheet while maintaining its immunomodulatory and tissue integration properties.